Assessing the skills of evaluation in the writings of postgraduates - Muhamad, Ainon Jariah; Engku Ibrahim, Engku Haliza; Esa, Zaleha (2013)
The ability to write critically is a very important aspect of university writing. This critical writing skill is crucial for postgraduates as they need to write critical reviews of a book, a chapter, or a journal article, especially those pertinent to their area of study. Writing a critical review usually requires reading the selected text in detail, summarising, evaluating and also reading other related texts so that students can present a fair and reasonable evaluation of the selected text. The objective of this paper is to investigate whether the postgraduate students are able to apply the skills of evaluation in writing a critical review of selected texts. Critical review papers of fifteen postgraduate students of an international university in Malaysia will be collected, assessed and analysed. The study is expected to reveal the lack of skills and strategies in writing effective critical reviews.